Exploring Family Needs in Pediatric Intensive Care Units: A Comparative Analysis between COVID-19 Isolation and Non-Isolation Settings - Septika, Rahmadevita; Fitri, Rhahmadiani; Ammelda, Rahmatika; Sari, Rahmadia (GoAcademica Research & Publishing, 2024)
This article aims to analyze the differences in family needs that arise when children are treated in the COVID-19 Isolation PICU and the COVID-19 Non-Isolation PICU. This research was conducted in the period March 2020 to December 2021. This research is a quantitative study with a retrospective cohort approach. The sampling method used was Non-Probability Sampling. The number of samples for the two groups, namely the COVID-19 Isolation PICU and the COVID-19 Non-Isolation PICU at RSUP DR M Djamil Padang, was 62 people. By detailing aspects such as closeness to the patient, service guarantees, mental support, information, and comfort, this research explores the impact of the pandemic situation on families' experiences during their child's intensive care. The research used quantitative methods with a retrospective cohort study at RSUP DR M Djamil Padang, involving patient families from both groups. The data collection instrument used the Critical Care Family Need Inventory (CCFNI) questionnaire, which was translated into Indonesian. Data analysis was carried out by comparing the frequency distribution of family characteristics, length of stay, and family needs through relevant statistical tests.